2009
DOI: 10.1590/s0103-64402009000200010
|View full text |Cite
|
Sign up to set email alerts
|

Fracture strength of teeth restored with ceramic inlays and overlays

Abstract: This study evaluated the fracture strength of teeth restored with bonded ceramic inlays and overlays compared to sound teeth. Thirty sound human maxillary premolars were assigned to 3 groups: 1-sound/unprepared (control); 2-inlays and 3-overlays. The inlay cavity design was Class II MOD preparation with an occlusal width of 1/2 of the intercuspal distance. The overlay cavity design was similar to that of the inlay group, except for buccal and palatal cusp coverage The inlay and overlay groups were restored wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 12 publications
(42 reference statements)
2
27
0
3
Order By: Relevance
“…3,4 However, a recurrent question regarding inlay restorations relates to cavity design, especially regarding the occlusal isthmus extension, and to when the cusps should be overlapped. 5,6,7,8,9 In the literature, recommendations can be found indicating that when the limits of the inlay cavity preparations are closer than 1.5 mm to the functional cusp, or when there is a less than 2 mm remaining thickness, an onlay preparation should be included, with a 2 mm axial reduction. 10 This principle of cavity preparation with cuspal coverage or overlap is based on metal cast restorations that do not adhere to dental substrates, and that are recommended to strengthen a weakened tooth declaration of interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, a recurrent question regarding inlay restorations relates to cavity design, especially regarding the occlusal isthmus extension, and to when the cusps should be overlapped. 5,6,7,8,9 In the literature, recommendations can be found indicating that when the limits of the inlay cavity preparations are closer than 1.5 mm to the functional cusp, or when there is a less than 2 mm remaining thickness, an onlay preparation should be included, with a 2 mm axial reduction. 10 This principle of cavity preparation with cuspal coverage or overlap is based on metal cast restorations that do not adhere to dental substrates, and that are recommended to strengthen a weakened tooth declaration of interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…reported that fracture strength of teeth restored with inlay and onlay ceramics are near to normal teeth. 48 Dejak et al . also reported that adhesively bonded composite resin and ceramic inlay reinforce the structure of the posterior teeth.…”
Section: Discussionmentioning
confidence: 99%
“…2) There was no support found for the practice of replacing large amalgam and resin composite restoration with onlay or crowns to prevent potential tooth fractures. 3) Indirect anterior restorations with ceramometal crowns were more cost-effective than porcelain jacket crowns [50].…”
Section: Discussionmentioning
confidence: 99%